Smart legislative regulation: investigation of the behavior of the Czech RIA Committee - Janáček, Julius; Pacovský, Libor; Jílková, Jiřina; Jílek, Jindřich (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: This article studies the behavior of the Czech Regulatory Impact Assessment (RIA) Committee during the years between 2013–2018. This institution assesses RIAs of new laws and regulations which are in the process of ratification. Aim: The main aim was to find if the legislative change of February 3, 2016 had a direct impact on the decision-making of the Committee. Further, we ask whether there are other distinct patterns in the behavior of Czech RIA Committee members. Specifically, do the RIA Committee’s verdicts become more negative with time? We also investigate the level of independence of the Committee. In our analysis we used basic statistics: Chi-Square test of independence and regression analysis. To complete our study, we used data from a questionnaire which was distributed among RIA Committee members. Results: In our analysis we found that the legislative change did not have a direct immediate effect on the RIA Committee of the Czech Republic. However, we discovered that the RIA Committee has lost most of its independence and power in the six years of its existence. This change was gradual and most likely catalyzed by pressure from politicians. Further, voting per rollam yielded more positive results. We also discovered an institution whose RIA Committee verdicts differed significantly. Based on the findings of our research, we offer recommendations to the RIA Committee and other institutions with a similar purpose.